E-Modul Dasar Pemrograman berbasis Android sebagai Media Pembelajaran Bahasa Bahasa C++ - Uska, Muhammad Zamroni; Wirasasmita, Rasyid Hardi; Kholisho, Yosi Nur (Educate : Jurnal Teknologi Pendidikan, 2023)
The basis of programming is to master the basic programming languages, one of which is C++. However, in its application, Hamzanwadi University students are constrained in understanding the C++ language due to the syntax and structure of C++, and the modules used are less specific in content. Our research’s objective is to design/develop an android-based C++ programming base e-module while taking into account user feedback on how well users comprehend the fundamental ideas behind the C++ language. ADDIE is the model used to create this E-module, and the type of data used is quantitative. Questionnaires were used to collect the data, which was then quantitatively examined. 22 users and students who attended lectures on basic programming served as the study’s subjects.. Our findings suggest that this product has a menu in it: intro page, material menu page, main menu page, video menu, hint menu, and profile menu. The findings of the media experts’ assessment came in at 83% (very plausible), and the results of the material experts’ assessment came in at 85%. (very feasible). Meanwhile, there was a strong response. Users scored 83% and were labeled as having extremely high proficiency. A high-quality medium or application is deserving of usage and has a very high response rate, allowing users to advance their understanding of C++ programming.